2018
DOI: 10.4103/0366-6999.232790
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence of Ovarian Endometriosis in Chinese Patients Aged 45 and Over

Abstract: Background:When considering the issue of recurrence, perimenopausal women may have more dilemma during management comparing with young women, for example, whether to retain the uterus and ovary during surgery, whether it is necessary to add adjuvant medicine treatment after operation, and there is no evidence for reference about using of gonadotropin-releasing hormone agonist. This study aimed to study the risk factors for the recurrence of ovarian endometriosis (EM) in patients aged 45 and over.Methods:This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Two previous studies reported the recurrence rates of ovarian endometrioma in women aged 40-49 years. He et al reported that the cumulative recurrence rate was 10.0% at 1 year and 27% at 5 years after surgery in patients aged 45 years higher, and that the risk of recurrence was reduced with post-operative treatment and increased by ovarian preservation 9 . However, this study included oophorectomized patients and used a different definition of recurrence, as not only sonographic findings but also recurrent pain symptoms and elevated serum CA125 level were considered as signs of disease recurrence 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies reported the recurrence rates of ovarian endometrioma in women aged 40-49 years. He et al reported that the cumulative recurrence rate was 10.0% at 1 year and 27% at 5 years after surgery in patients aged 45 years higher, and that the risk of recurrence was reduced with post-operative treatment and increased by ovarian preservation 9 . However, this study included oophorectomized patients and used a different definition of recurrence, as not only sonographic findings but also recurrent pain symptoms and elevated serum CA125 level were considered as signs of disease recurrence 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Various medical conditions such as hypertension, diabetes mellitus, thromboembolic disease, cardiovascular problems, and osteoporosis are more frequent in this group than in younger women. Moreover, no age-based drug administration guidelines exist, and few studies have investigated the recurrence rate of ovarian endometrioma in women aged 40–49 years or differences in recurrence rates according to post-operative medication 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found other possible risk factors that influencing the recurrence of endometrioma. Ovarian preservation was an independent risk factor for postoperative recurrence of endometrioma over 45 years old [ 35 ]. The depth of endometrial tissue infiltration into the cyst wall was a risk factor for endometrioma recurrence, and the optimal cut-off value was 1.2 mm, at which time the sensitivity was 62.9% and the specificity was 75% [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography was used to determined postsurgical EMs recurrence. Recurrent endometrioma was defined as the presence of ovarian cyst (≥2 cm in diameter) that has a thin wall and homogenous low echogenic fluid signal, the cyst does not disappear after several menstrual cycles in ultrasound 13 . The patients will perform pelvic magnetic resonance imaging if the ovarian mass was not typical on ultrasound.…”
Section: Methodsmentioning
confidence: 99%